Visceral uric gout in an adult Aburria jacutinga - Clara Rocha Barreto Corrêa Manhães; Karen dos Santos Barreto Rangel; Carlos Ramón Ruiz-Miranda (Pubvet)
Visceral uric gout is a metabolic disorder characterized by the accumulation of urate crystals on the serous surfaces of the coelomic cavity and in the kidneys. In the present study, we describe a case of visceral uric gout in an adult black-fronted piping guan (Aburria jacutinga) under human care. Macroscopic findings showed urate crystals in the mesentery, pericardium, liver, and kidneys. The kidneys were enlarged, and the vessels of the right kidney were congested. Microscopically, we observed the presence of fine crystals with the appearance of "needles". The lesions found are compatible with those previously described in the literature for visceral uric gout syndrome in birds. This is the first report of visceral uric gout in Aburria jacutinga.